Incidence and types of acute viral hepatitis in Newcastle upon Tyne. Issue 757 (November 1988) - Hosker, H. S.; Lindsay, D. C.; Game, F.; Codd, A. A.; Dale, G.; Record, C. O.
Abstract : The incidence and types of viral hepatitis in the city of Newcastle upon Tyne have been studied by serological analysis of (a) all blood samples sent to the virological laboratory for hepatitis testing and (b) all blood samples sent by general practitioners to the biochemical laboratory for liver function testing. The annual detection rate of acute viral hepatitis was found to be 31.5 cases/100, 000 population, of which 9.1 were hepatitis B. Only three sporadic cases of non-A non-B hepatitis were identified. The incidence of hepatitis is at least four-fold greater than suggested by notification rates and may be substantially higher as general practitioners rarely requested laboratory confirmation of household contacts of index cases.